Analysis of Working Capital Budget and Profitability at PT. Hadji Kalla, Palopo Branch - S. Sudirman; Henri Fauli; Umar Hi Salim (Golden Ratio of Data in Summary, 2026)
The objective of this research is to determine and analyze the working capital turnover in increasing profitability at PT. Hadji Kalla, Palopo Branch. The research method used in this study is quantitative data. Quantitative data in this study includes the company's financial statements in the form of balance sheets and profit and loss statements. Data sources for this study used primary and secondary data. Primary data, namely data obtained through observation and interviews, aimed at refining this paper. Secondary data, namely data obtained from other parties or indirectly from the primary source (the company) related to the research problem. The company's financial data to be studied spans five years, from 2012 to 2016. The results of the study explain that cash turnover, inventory turnover, and accounts receivable contribute to increasing profitability at PT. Hadji Kalla Palopo Branch has been quite effective this is because the number of company sales activities has increased annually and the profitability ratio measured by ROE, ROI, NPM is quite good according to the standards of experts. The standards for ROE, ROI, NPM according to Lestari and Sugiarto 2007 are good, namely > 2% based on the proposed hypothesis which states that cash turnover and receivables turnover at PT. Hadji Kalla Palopo Branch have not been able to increase the company's profitability so that the proposed hypothesis is accepted because cash turnover and receivables are not efficient.